A lei do superendividamento como instrumento de proteção do consumidor de crédito - Tritapepe, Rodrigo (2024)
The aim of this study is to analyze the effectiveness of legal provisions on suppliers' duties in granting so-called responsible credit in their various “products”. The idea of responsible credit is to exercise good faith to its fullest potential, placing the supplier in the consumer's place and serving the latter as a guardian, caretaker of their financial health. On the contrary, what is perceived is the exercise of exacerbated harassment by financial institutions in granting credit in an irresponsible, misleading manner, discarding and ignoring the guiding principle of consumer relations, the vulnerability and hypervulnerability of the consumer. From the elderly to young people at an early age, victims of a system of “imprisonment” where more and more money is owed to those who offer instant credit, such as in cases where loans are granted with the click of an application. The objective of the work is focused on analyzing the new legislation and doctrine to verify in the end whether the August 2021 legislation was sufficient to curb commercial practices that were already in complete non-compliance with consumer protection.